2022
DOI: 10.3390/children9020226
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Use of Teaching Strategies for Fundamental Movement Skills in Primary School Physical Education Programs

Abstract: Fundamental motor/movement skills (FMS) describe the basic skills necessary to complete physical tasks, and are a key aspect of primary school physical education (PE) programs. Yet, specific teaching styles for FMS development have been relatively unexplored. Through a mixed-methods design, experiences and perceptions of different PE teachers (preservice, specialist, and generalist) were explored. The Spectrum of Teaching Styles (STS) survey was used to quantify self-reported use of teaching styles that may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…In fact, a study showed that teachers with a high intrinsic motivation more frequently adopt student-oriented approaches and production teaching styles, while teachers not autonomously motivated adopt teacher-centered approach and reproduction teaching styles usually (38). Moreover, recent studies showed that senior PE teachers failed to use a wide range of teaching styles during their lessons (39), preferring the Practice Style due to its ability to facilitate activities and provide feedback, and allowing students to exercise motor skills and receive immediate feedback (40,41). The present study is conducted on secondary school PE teachers who participated in the Regional Observatory of Motor Development and Health Behavior Project.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study showed that teachers with a high intrinsic motivation more frequently adopt student-oriented approaches and production teaching styles, while teachers not autonomously motivated adopt teacher-centered approach and reproduction teaching styles usually (38). Moreover, recent studies showed that senior PE teachers failed to use a wide range of teaching styles during their lessons (39), preferring the Practice Style due to its ability to facilitate activities and provide feedback, and allowing students to exercise motor skills and receive immediate feedback (40,41). The present study is conducted on secondary school PE teachers who participated in the Regional Observatory of Motor Development and Health Behavior Project.…”
Section: Discussionmentioning
confidence: 99%
“…On reflection, dividing the stakeholders up to work on different tasks based on their expertise could have been more advantageous to programme development. For example, PE specialists were more knowledgeable and had a greater understanding of the teaching and delivery of FMS [ 59 , 60 ], whereas the class teachers had greater knowledge of the pupils’ educational and pastoral needs [ 61 ]. As all the participating schools had PE specialists deliver their PE curricula, an alternative workshop approach would have been for the PE specialists to focus on the FMS element of programme development, and the school leaders and class teachers to focus on the psychosocial skills element.…”
Section: Discussionmentioning
confidence: 99%
“…al. believed that physical education teachers were more competent in demonstrating and experiencing movement and strategies, and were able to combine materials to improve students' FMS [53]. Secondly, da Silva stated that a wellstructured subject would likely achieve better motor competence as the teacher should optimize the intervention in developing students' FMS [54].…”
Section: Fundamental Motor Skillsmentioning
confidence: 99%